2014
DOI: 10.1016/j.anr.2014.04.002
|View full text |Cite|
|
Sign up to set email alerts
|

Concept Analysis of Empowerment in Old People with Chronic Diseases Using a Hybrid Model

Abstract: The concept analysis of empowerment showed some of the required conditions for the empowerment of older people with chronic diseases in nursing care, which have not been mentioned in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 33 publications
2
53
0
3
Order By: Relevance
“…Seventeen definitions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Chart 1) and seven dimensions (9,14,(24)(25)(26)(27)(28) of empowerment (Chart 2), and 10 empowerment measures (9,13,24,(29)(30)(31)(32)(33)(34)(35) (Chart 3) were selected. The analysis showed that the concept of empowerment has been broadly used in the health sciences field, especially over the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen definitions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Chart 1) and seven dimensions (9,14,(24)(25)(26)(27)(28) of empowerment (Chart 2), and 10 empowerment measures (9,13,24,(29)(30)(31)(32)(33)(34)(35) (Chart 3) were selected. The analysis showed that the concept of empowerment has been broadly used in the health sciences field, especially over the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…Fotoukian et al, 2014 (14) personal control, self-regulation, all of which have a generally equivalent meaning. The latter characteristics are considered individual attributes, and one can only talk of empowerment when these processes have an impact on the community, that is, when individuals actively participate in the community or organization (38)(39) .…”
Section: Definitions Referencesmentioning
confidence: 99%
“…This was a study with a qualitative design and concept analysis method with hybrid model approach in three phases: theoretical, fieldwork, and a final analytical approach with the help of deductive-inductive reasoning (15). Using the method that was described by Walker and Avant (2005), the authors clarify the concepts that are vague and have multiple meanings in different contexts.…”
Section: Methodsmentioning
confidence: 99%
“…특히, 유방암 여성들은 자가관리를 위해서 동병상련을 나눌 수 있는 자조집단 활 동에 참여하고 [13], 유방암 인식 개선과 유방암 여성의 권익 향상을 위한 핑크리본 캠페인에 동참하고 있다 [14]. 유방암 [8,23,27], 여성성 수용 [28], 자기통제 [6,8,22,27,28], 자기효능 [17,19,23,27], 자기결정 [8,17,23] 으로 하였고, 이는 유방암으로 인해 손상된 여성성을 긍정적으로 회 복하고 목적 달성을 위하여 자율적인 선택을 시행하며 자신의 삶을 조절하고자 하는 주도적인 역량을 의미한다. 상호작용적 요인의 개 념적 지표는 가족 대인관계 [5,10], 동료 대인관계 [7,10,23,27], 의료 인 대인관계 [7,9,18,20,21] Figure 2).…”
unclassified